The psychological aspect of time dynamics in the Kalmyk thangka of the Green Tara - N. A. Bardaeva (Nomadic Civilization: Historical Research)
The article presents the author’s interpretation of the information space of the ancient Kalmyk tanka Green Tara, created for the 300th anniversary of the Romanov dynasty, which was celebrated in the Bolshederbetovsky ulus in 1913. There is no doubt that the creation of the iconographic image of Green Tara was a deeply thought-out act of the Buddhist clergy and sovereign noyons of the Bolshederbetovsky ulus in whose power was the ulus. The object of this study is the Kalmyk tanka “Green Tara” as a Buddhist monument of the pre-revolutionary period of cultural and religious life in the Kalmyk steppe. The purpose of the author is to show the versatility and spiritual significance of the Buddhist icon “Green Tara” in the life of the Kalmyk people, its role in the formation of national ethno-religious consciousness in the aspect of Buddhist psychology. The article discusses the history of its creation, analyzes its artistic, cultural and iconographic features. The relevance of this topic is due to the author’s approach to the study of the symbolism of Buddhist iconography in the psychological aspect on the example of the traditional image of the Bodhisattva Green Tara. The psychological interpretation of the information field of the Kalmyk tanka is an absolutely new direction in the study of Buddhist iconography, which opens up a huge field for further understanding.